Unusual and Fatal Case of an Undiagnosed Intravascular Large B‐cell Lymphoma: The Oncologist's Great Imitator†. Issue 1 (30th July 2019) - Barranco, Rosario; Caputo, Fiorella; Bedocchi, Davide; Frigiolini, Francesca Maria Elena; Castelletti, Lara; Fraternali Orcioni, Giulio; Ventura, Francesco
Abstract: Intravascular lymphoma (IVL) is a rare subtype of extranodal lymphomas that is characterized by the selective growth of neoplastic cells within the lumen of small vessels. Authors document the case of an unexpected death caused by an undiagnosed intravascular large B‐cell lymphoma with multi‐organ involvement, which had initially manifested as an infection and then as an unclarified central nervous system pathology. Histological examination showed a diffuse intravascular large B‐cell brain lymphoma with prominent cerebral involvement. The relevance of the case report reveals the importance of an autopsy of an extremely rare and threatening pathology that in most cases is diagnosed only postmortem. As a result, the role of the forensic pathologist becomes particularly important. When specifically performing an in‐depth autopsy evaluation with a specific histologic analysis, it is possible to identify the intravascular lymphoma and declare a more accurate cause of death.